THE PERFORMANCE OF LMS USE AND ITS IMPACT ON ENGLISH LEARNING OUTCOMES - Hefri Asra Omika (Edulingua: Jurnal Linguistiks Terapan dan Pendidikan Bahasa Inggris, 2023)
Learning management systems (LMS) are strong integrated systems that help teachers and students complete a range of tasks during the online learning process. For three semesters, the SMAN Titian Teras twelfth graders have used LMS Moodle to learn English. This study aims to (1) describe the accomplishment of twelfth-grade students' online English learning activities using LMS Moodle; (2) identify differences in twelfth-grade students' English learning outcomes based on LMS Moodle performance, and (3) identify differences in twelfth-grade students' English learning outcomes based on gender. The population of this research is grade 12 students of SMA Negeri Titian Teras H. Abdurrahman Sayoeti in the academic year 2021/2022, totaling 336 students. The sampling method used was simple random sampling, based on the Slovin formula, 182 students were assigned as the research sample. Data collection instruments used in this study: (1) Moodle log data which shows student performance in learning using LMS Moodle; and (2) computer-based semester exam results data on English subjects. Analysis of performance data using the LMS Moodle using the Sum Activity Rating (SAR) instrument developed by Singh et al. The statistical test used in this study is the Mann-Whitney U Test. The results showed that the level of achievement of the twelfth-grade students' English learning activities was high (84.3%). The English learning outcomes of students who have high LMS usage performance are better than students who have low LMS usage performance. English learning outcomes of female students are better than male students.